2007
DOI: 10.1177/08857288070300010501
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Evaluation of a Vocational Support Program for Adults on the Autism Spectrum

Abstract: A utism spectrum disorders (ASD) are characterized by impaired social interaction, a restricted repertoire of activities and interests, and impaired communication (except for relatively normal language use by individuals with Asperger syndrome; American Psychiatric Association, 1995). Several studies have demonstrated progression of skills among children with autism following early intervention, including language gains, improved social interaction, and significant IQ gains (Rogers, 1996). Whereas early interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
153
0
15

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(173 citation statements)
references
References 12 publications
5
153
0
15
Order By: Relevance
“…Mawhood and Howlin (1999) emphasized a close liaison between VR service providers and employers which would allow for exploring possible job opportunities and matching the skills and abilities of the employee with a suitable job. Hillier et al (2007a) indicated that higher parental involvement and family support could lead to better employment outcomes for individuals with ASD. Self-determination as well as autonomy of individuals on the spectrum are also important in the collaboration (Carter et al 2012;Test et al 2014).…”
Section: Multidisciplinary Collaborationmentioning
confidence: 99%
“…Mawhood and Howlin (1999) emphasized a close liaison between VR service providers and employers which would allow for exploring possible job opportunities and matching the skills and abilities of the employee with a suitable job. Hillier et al (2007a) indicated that higher parental involvement and family support could lead to better employment outcomes for individuals with ASD. Self-determination as well as autonomy of individuals on the spectrum are also important in the collaboration (Carter et al 2012;Test et al 2014).…”
Section: Multidisciplinary Collaborationmentioning
confidence: 99%
“…They may include understanding complex job application materials; 'thinking on their feet' in an interview; acclimatising to new procedures and routines; remembering and following instructions; responding flexibly to unexpected situations; planning and juggling multiple tasks; communicating effectively with co-workers; interacting socially; and managing sensory sensitivities in the workplace (Beardon & Edmonds 2007;Hillier et al 2007;Stuart-Hamilton et al 2009;Robertson 2010). Stankova and Trajkovski (2010) note that these generalised deficits mean some types of work are likely to be unsuitable for the majority of adults with ASD.…”
mentioning
confidence: 99%
“…In addition to their specific job skills, there is a popular view, borne out to some extent by empirical data, that adults with ASD exhibit many exemplary characteristics as employees, such as honesty, efficiency, precision, consistency, low absenteeism, and a disinterest in 'office politics' (Müller et al 2003;Hagner & Cooney 2005;Hillier et al 2007). …”
mentioning
confidence: 99%
“…The six active agencies (TEACCH, PCDI, Groden Network, Cove Center, Prospects and Autism Center for Excellence at Virginia Commonwealth) in this field that support adults with ASD so that they can enter the open labor market, have achieved significant progress in the employment sector. Firstly, their programs provide, to a sufficient extent, the services a vocational support program should offer, as reported in the research papers by Hillier et al (2007) and Wehman et al (2016).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a specialized supported employment program needs to provide the following services and forms of help to interested individuals with ASD: counseling; educational support and guidance; help with overcoming difficulties, such as communication problems with colleagues and employers; helping individuals to comply with social rules and to work independently; ensuring the individual remains in a post for at least six months, giving top priority to the individual's personal job satisfaction, and finally, providing counseling services to the members of services employing adults with ASD (Hillier, Campbell, Mastriani, Izzo, Kool-Tucker, Cherry, & Beversdorf, 2007).…”
Section: Introductionmentioning
confidence: 99%